Causal effect of gut microbiota metabolic pathways on CSAG1 expression in chondrosarcoma: a mendelian randomization analysis - Xiaoyun Liu; Sen Yang; Liyun Liu (BMC Cancer)
Abstract Background Changes in gut microbiota metabolism might play an important role in the development of some cancers. However, the causal relationships of gut microbiome-related metabolic pathways in chondrosarcomas and the specific pathways affected remain largely unknown. Methods We used two-sample bidirectional and multivariate Mendelian randomization (MR) to reveal a causal relationship between the gut microbiota metabolic pathway (GMMP) and chondrosarcoma associated gene 1(CSAG1) via the largest available genome-wide association study (GWAS). Results Univariate MR analysis revealed that tetrapyrrole biosynthesis from glutamate, menaquinol 6 biosynthesis, glycogen degradation II, 8-amino-7-oxononanoate biosynthesis, taxadiene biosynthesis, glycolysis and tRNA charging had a significant causal relationship with CSAG1.Multivariate MR analysis suggested that tetrapyrrole biosynthesis, menaquinol 6 biosynthesis, glycogen degradation II, glycolysis and tRNA charging still had a significant causal effect on CSAG1. According to the results of reverse MR analysis, no significant causal effect of CSAG1 on the GMMP was found. Conclusions This study offers further insights into the gut microbiota-mediated mechanism of chondrosarcoma development.